How to Increase E-Repurchase of E-Pay Consumers in Purwokerto - Monica Rosiana; Dwita Aprillia Floresti (Jurnal Akuntansi, Manajemen dan Ekonomi, 2020)
The purpose of this study is to explain the effect of perceived usefulness, perceived ease of use, perceived risk on e-repurchase using e-pay. Structural Equation Modeling (SEM) was used to test the empirical model. The number of samples in this study was 114 e-pay users in Purwokerto. The results indicate that perceived usefulness and perceived ease of use have a positive effect on e-repurchase. In addition, researchers can also prove that perceived risk has a negative effect on e-repurchase.